Combination of pseudoephedrine and emodin ameliorates LPS-induced acute lung injury by regulating macrophage M1/M2 polarization through the VIP/cAMP/PKA pathway - Wen-Ba Wang; Jing-Tao Li; Yi Hui; Jie Shi; Xu-Yan Wang; Shu-Guang Yan (BMC, 2022)
Abstract Background Acute lung injury (ALI) is an acute multifactorial infectious disease induced by trauma, pneumonia, shock, and sepsis. This study aimed to investigate the protective effects of pseudoephedrine and emodin combined treatment in experimental ALI, as well as the mechanisms underlying the regulation of inflammation and pulmonary edema via the VIP/cAMP/PKA pathway. Methods The wistar rats were randomly divided into fifteen groups (n = 5). Rats in each group were given intragastric administration 1 h before LPS injection. Those in the control and LPS groups were given intragastric administrations of physiological saline, rats in other groups were given intragastrically administered of differential dose therapeutic agents. The rats in the LPS and treatment groups were then injected intraperitoneally with LPS (7.5 mg/kg) to induce ALI. After being treated with pseudoephedrine and emodin for 12 h, all animals were sacrifice. Anal temperatures were taken on an hourly basis for 8 h after LPS injection. Pathological examination of lung specimen was performed by H&E staining. Cytokines (IL-1β, TNF-α, IL-6, iNOS, IL-10, Arg-1, CD86, CD206, F4/80, VIP) in lung tissue were assayed by ELISA and immunofluorescence. The expression of VIP, CAMP, AQP-1, AQP-5, p-PKA, PKA, p-IκBα, IκBα, p-p65, p65, p-P38, P38, p-ERK1/2, ERK1/2, p-JNK1/2, JNK1/2 protein in lung was determined by western blotting. Results After rats being treated with pseudoephedrine + emodin, reduced of fever symptoms. The contents of inflammatory cytokines (IL-1β, TNF-α, IL-6, iNOS) were decreased and anti-inflammatory cytokines (IL-10, Arg-1) were significantly increased in serum. Pseudoephedrine + emodin treatment effectively promoted VIP cAMP and p-PKA protein expression in lung tissues, and significantly inhibited NF-κB, MAPK phosphorylation, Pseudoephedrine + emodin treatment can inhibit M1 polarization and promoted M2 polarization via the VIP/cAMP/PKA signaling pathway. Conclusions The combination of Pseudoephedrine and emodin was effective in ameliorating LPS-induced ALI in rats by inducing VIP/cAMP/PKA signaling. Inhibiting the NF-κB, MAPK inflammatory pathway, relief of pulmonary edema suppressing macrophage M1 polarization, and promoting macrophage M2 polarization.